2018
DOI: 10.1103/physrevlett.121.058103
|View full text |Cite
|
Sign up to set email alerts
|

Time Irreversibility and Criticality in the Motility of a Flagellate Microorganism

Abstract: Active living organisms exhibit behavioral variability, partitioning between fast and slow dynamics. Such variability may be key to generating rapid responses in a heterogeneous, unpredictable environment wherein cellular activity effects continual exchanges of energy fluxes. We demonstrate a novel, noninvasive strategy for revealing nonequilibrium control of swimming-specifically, in an octoflagellate microalga. These organisms exhibit surprising features of flagellar excitability and mechanosensitivity, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 41 publications
2
85
0
Order By: Relevance
“…It is suggested that the primordium-facing membranelles act as pacemakers [34]. As in some species of algal multiflagellates [36,37], calcium signalling via contractile elements can dynamically reverse the beating direction of the membranelles [38]. Addition of digitoxin and other chemicals directly modulates intermembranellar connectivity leading to a change in MCW wave velocity but affects the beat frequencies to a lesser extent [39].…”
Section: (B) Infraciliature and Hydrodynamic Interactionsmentioning
confidence: 99%
“…It is suggested that the primordium-facing membranelles act as pacemakers [34]. As in some species of algal multiflagellates [36,37], calcium signalling via contractile elements can dynamically reverse the beating direction of the membranelles [38]. Addition of digitoxin and other chemicals directly modulates intermembranellar connectivity leading to a change in MCW wave velocity but affects the beat frequencies to a lesser extent [39].…”
Section: (B) Infraciliature and Hydrodynamic Interactionsmentioning
confidence: 99%
“…Knowledge of this beat could provide hitherto untapped information for the estimation of non-visible attributes such as the contribution of different metabolic path-ways, and modulation in response to the physical and biochemical environments (Ooi et al, 2014). The capability to capture flagellar movements and associated mechanistic insights has broader applicability in the life sciences including the role of cilia in embryonic development (Smith et al, 2019), swimming of multiflagellate microorganisms (Wan and Goldstein, 2018), the use of high-speed holographic microscopy to image the flagellar waveforms of malaria parasites (Wilson et al, 2013), and even the design of hybrid bio-robots for biomedical applications (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For the same cell, beating can be restricted to a subset of flagella with the remaining flagella quiescent. Asymmetries arising from the actively beating In (e), the octoflagellate Pyramimonas octopus undergoes reorientation following a shock response (see also [26]). (f) A P. parkeae cell presenting a single actively beating flagellum.…”
Section: Gait-switching and Partial-activationmentioning
confidence: 99%